The efficacy of acupuncture and moxibustion for early and middle-stage osteonecrosis of the femeral head: A systematic review and meta-analysis of randomized controlled trials. Issue 22 (4th June 2021) - Jin, Hongguang; Li, Linhui; Yu, Wen; Fu, Yong
Abstract: Background: Osteonecrosis of the femeral head (ONFH) occurs predominantly in young- and middle-aged people, and the disability rate is high in the late stage of the disease and most patients have to undergo total hip replacement. Clinically, increasing attention is paid to intervening early and middle-stage ONFH so as to delay its progress. Acupuncture and moxibustion (AM) is a unique method for treating ONFH in China. This study aims to summarize the advantages of AM for the treatment of ONFH. Methods: A comprehensive literature search was conducted on the database with languages of English and Chinese. The medical subject titles used are "Osteonecrosis of the femoral head" and "acupuncture and moxibustion." Related words in the title or abstract including but were not limited to "necrosis of the femoral head, " "avascular necrosis of the femoral head, " "ischemic necrosis of the femoral head, " "caput femoris necrosis, " "bone paralysis, " "bone erosion, " and "bone atrophy." Results: Nine randomized controlled trials were identified in this meta-analysis that included 630 subjects. Meta-analysis showed that the trial group that treated with conventional therapy combined with AM had a higher effective rate ( Z  = 2.27 P  = 0.02) and excellent and good rate ( Z  = 4.85 P  < 0.00001) and Harris hip function score (HHS) ( Z  = 2.31 P  = 0.02) and lower incidence of related adverse reactions during treatment ( Z  = 2.82 P  = 0.005) compared with the control group that treated with conventional therapy alone. Conclusions: AM for early and middle-stage ONFH is an effective and relatively safe intervention, which can improve the effective rate and excellent and good rate and HHS, and reduce the adverse reaction rate. Clinically, early and middle-stage ONFH can be intervened by combining with AM while taking conventional therapy to improve the efficacy.